INVESTIGATING THE SPATIAL ORGANIZATION TRADITIONAL NEIGHBORHOODS OF HAMEDAN AND ITS IMPACT ON SOCIAL RELATIONS - Jamebozorg, Zahra; Najafi, Araz; Fakhar, Zarrin (Revista Ciências Humanas, 2020)
Hamadan's traditional neighborhoods organize and shape the basic spatial structures of architecture and urbanization of the Qajar era, which have undergone many changes over the course of the city's development plans, and their traditional structure has changed over time due to non-compliance. They are worn out and have lost their functionality, which has reduced the level of communication between the residents. Hamadan neighborhoods in the Qajar period have been identified and evolved in two forms: linear, field, mosque, lawn, bath, caravansera, Imamzadeh, Sardabeh, Cheshmeh, etc. The center of the neighborhood was the heart of the neighborhood. Shops built around it.